Comparing technical efficiency of maize smallholder farmers in Tabora and Ruvuma regions of Tanzania: a frontier production approach - Miho , Asela (Asian Journal of Agriculture and Rural Development, 2018)
Technical efficiency was considered in comparing production efficiency of maize crops among smallholder farmers in Tabora and Ruvuma regions respectively, using maximum likelihood estimation (MLE) and ordinary least square (OLS) on Cobb-Douglas production function and OLS on technical inefficiency model in STATA 12 on the National Sample Census of Agriculture 2007/2008 data. Findings indicated that, Tabora smallholder farmers were more technically efficient with mean technical efficiency of 61% compared to 53% of Ruvuma farmers. Actual planted area came as the most important factor that increased maize output and Tractor asset being the most in optimal used factor ‘keeping other factors constant’, in both regions. From the technical inefficiency model; Age, household size, primary education and inputs costs increased technical inefficiency while credit access, capital assets, good living condition and crop farming as main activity increased technical efficiency in both regions. Thus, the support and sensitization from government and other development partners for agricultural development should be area specific particularly where there is high technical efficiency of the given crop. In optimal use of Tractor among smallholder farmers should be taken as a policy issue; for despite the efforts taken by stakeholders its influence to output attained among smallholders is insignificant.